Designing fish optic mobile application for fish disease identification / Romiza Md Nor ... [et al.] - Md Nor, Romiza; Abdullah, Muhammad Amin; Aminuddin, Nurul Syafiqah; Sharifunizam, Nur Shahidatul Shaurah; Zainal, Aliaa Zafirah; A Hamid, Huzaifah (UiTM Cawangan Perlis, 2022)
The signs and symptoms of fish disease can be traced by checking on the eye surface which is the cornea of fisheye. The Fish Optic mobile application aims to help students study the fisheye anatomy and to trace the symptoms of diseases on fish. The Fish Optic user mobile application uses Human-Centered System Development Life Cycle (HCSDLC) which consists of four phases which are project selection and planning, analysis, design and implementation. As HCSDLC emphasizes on user involvement throughout all phases, an interview was conducted, and a post task walkthrough was performed. User Acceptance Test formative evaluation was then conducted by distributing questionnaire. Some recommendations are also discussed for future works to improve and refine the design of the Fish Optic mobile application to enhance user experience. It can be concluded that using HCSDLC method throughout the design of Fish Optic mobile application contributes to a well-defined systems requirement to support user needs and to accommodate the lack of human understanding that frustrates users in their daily routines.